Pengaruh Kesejahteraan Karyawan terhadap Motivasi Kerja Karyawan pada RSU Rachma Husada Bantul Yogyakarta - Suhartini, Yati; Septiningsih, Tri (Akmenika, 2014)
This research examines the effect of employee welfare programs of economical, welfare programs of facilities and programs of service to employee motivation in Rachma Husada Bantul hospital. The population of this study are 104 employees who are 82 employees used as the samples of the research. Data were collected by using a questionnaire and analyzed by using multiple regressions which is also applied for testing the 4 hypotheses. All of the process analyses are assisted by SPSS programs. The results of analyses show that : (1) there is a positive but not significant between welfare programs of economical to employee motivation indicated by the value of β1 0.055, t value 0.465 and sig. 0.643. (2) there is a positive effect of welfare programs of facilities to employee motivation indicated by the value of β2 0.452, t value 3.503 and sig. 0.01. (3) there is a positive effect of welfare programs of service to employee motivation indicated by the value of β3 0.305, t value 3.174 and sig. 0.02. and (4) there is a positive effect of welfare programs of economical, welfare programs of facilities and welfare programs of services to employee motivation indicated by the value of F 26.528, sig. 0.000. Finally, the value of adjusted R2 is 0.486. This means that 48.6% of employee motivation are explained by welfare programs of economical, welfare programs of facilities and welfare programs of service. Where as 51.4% of them are explained by other factors not examined in this study.